2021
DOI: 10.1111/jfbc.13705
|View full text |Cite
|
Sign up to set email alerts
|

Bovine milk extracellular vesicles induce the proliferation and differentiation of osteoblasts and promote osteogenesis in rats

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 42 publications
(45 reference statements)
0
25
0
1
Order By: Relevance
“…In an ensuing study, Oliveira et al showed that milk exosomes treatment on murine bone marrow cells induced an increase in osteoclast differentiation along with an inhibition of the osteoclast activity [ 149 ]. Recent research conducted by Go et al studied the addition of bovine milk exosomes to human osteoblastic Saos-2 cells in vitro, observing an increase in Saos-2 cells proliferation in a time-dependent and dose-dependent manner while promoting the expression of the osteoblast transcription factors RUNX2 and Osterix [ 150 ]. Moreover, treatment of Saos-2 and MC3T3-E1 pre-osteoblastic cells with milk exosomes increased alkaline phosphatase (ALP) and osteocalcin (OCN) levels, which are involved in extracellular matrix synthesis processes [ 150 ].…”
Section: Beneficial Effects Of Bovine Milk Exosomes On Overall Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…In an ensuing study, Oliveira et al showed that milk exosomes treatment on murine bone marrow cells induced an increase in osteoclast differentiation along with an inhibition of the osteoclast activity [ 149 ]. Recent research conducted by Go et al studied the addition of bovine milk exosomes to human osteoblastic Saos-2 cells in vitro, observing an increase in Saos-2 cells proliferation in a time-dependent and dose-dependent manner while promoting the expression of the osteoblast transcription factors RUNX2 and Osterix [ 150 ]. Moreover, treatment of Saos-2 and MC3T3-E1 pre-osteoblastic cells with milk exosomes increased alkaline phosphatase (ALP) and osteocalcin (OCN) levels, which are involved in extracellular matrix synthesis processes [ 150 ].…”
Section: Beneficial Effects Of Bovine Milk Exosomes On Overall Healthmentioning
confidence: 99%
“…Recent research conducted by Go et al studied the addition of bovine milk exosomes to human osteoblastic Saos-2 cells in vitro, observing an increase in Saos-2 cells proliferation in a time-dependent and dose-dependent manner while promoting the expression of the osteoblast transcription factors RUNX2 and Osterix [ 150 ]. Moreover, treatment of Saos-2 and MC3T3-E1 pre-osteoblastic cells with milk exosomes increased alkaline phosphatase (ALP) and osteocalcin (OCN) levels, which are involved in extracellular matrix synthesis processes [ 150 ]. Finally, the authors administered 50 mg/kg/day of exosomes to rats for 14 days and reported that the treatment was associated with significantly increased bone mineral density in trabecular and cortical tibiae [ 150 ].…”
Section: Beneficial Effects Of Bovine Milk Exosomes On Overall Healthmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 258 ] Cow Promotion of osteogenesis via proliferation and differentiation of osteoblasts in vitro (Saos-2 cell line) and in vivo (Sprague Dawley rats). [ 259 ] Cow Improved small intestinal dysfunction in malnutrition C57BL/6J mouse model. [ 260 ] Cow Enhancement of curcumin cell uptake and permeability in an intestinal model in vitro (Caco-2 cell line).…”
Section: Biological Effects Of Milk-derived Evsmentioning
confidence: 99%
“…Regulation of BMP2/CBFA1 signaling molecules by SOS induced the construction of bone mineralized matrix. In postmenopausal osteoporosis, the homeostasis between osteoblast and osteoclast is destructed due to estrogen deficiency, leading to decline of osteogenesis (Eastell et al, 2016; Go, Jeon, Lee, Lee, & Lee, 2021). We found that SOS promoted osteogenesis BMP2 involved signaling in postmenopausal osteoporotic mice.…”
Section: Resultsmentioning
confidence: 99%